Species profiles : life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest) : ghost shrimp and blue mud shrimp - Hornig, Susanna; Sterling, Anita; U.S.National Wetlands Research Center; Stanley D. (Stanley DeWitt) Smith; U.S. Army Engineer Waterways Experiment Station. Coastal Ecology Group,; U.S.National Wetlands Research Center (Biological report (Washington, D.C.) ;, 1989)
Keywords: Alsea Bay; Chetco River estuary; Columbia River estuary; commercial fisheries - shellfish; Coos Bay; Coquille Bay; crustaceans; fecundity; general; Ghost shrimp = Neotrypaea californiensis (Callianassa californiensis); growth; life history information; Mud shrimp = Upogebia pugettensis; Nehalem Bay; Nestucca Bay; Netarts Bay; recreational fisheries - shellfish; reproductive behavior; Rogue River estuary; Salmon River Estuary; Sand Lake; Siletz Bay; Siuslaw Bay; taxonomy; Tillamook Bay; Umpqua River estuary; Yaquina Bay

Species Profiles: Life Histories and Environmental Requirements of Coastal Fishes and Invertebrates (Pacific Northwest) : Dungeness Crab - Pauley, Gilbert B.; Armstrong, David A.; Heun, Thomas W. (Biological Report (Washington, D.C.), 1986)
Keywords: Alsea Bay; Chetco River estuary; Columbia River estuary; commercial fisheries - shellfish; Coos Bay; Coquille Bay; crustaceans; Dungeness crab = Metacarcinus magister (Cancer magister); fecundity; general; growth; life history information; Nehalem Bay; Nestucca Bay; Netarts Bay; recreational fisheries - shellfish; reproductive behavior; Rogue River estuary; Salmon River Estuary; Sand Lake; Siletz Bay; Siuslaw Bay; taxonomy; Tillamook Bay; Umpqua River estuary; Yaquina Bay

The Dungeness Crab Fishery in Oregon Estuaries - Oregon. Dept. of Fish and Wildlife. Marine Region, (1977)
Keywords: abundance; Alsea Bay; catch statistics; Chetco River estuary; Columbia River estuary; commercial fisheries - shellfish; Coos Bay; Coquille Bay; crustaceans; Dungeness crab = Metacarcinus magister (Cancer magister); life history information; natural resource management; Nehalem Bay; Nestucca Bay; Netarts Bay; recreational fisheries - shellfish; Rogue River estuary; Salmon River Estuary; Sand Lake; shellfish; Siletz Bay; Siuslaw Bay; Tillamook Bay; Umpqua River estuary; Yaquina Bay

Methods of supplementing clam and abalone production: annual report July 1, 1975 to June 30, 1976. Completion report 1975/1975- 1973/1976 - Gaumer, Thomas F.; Lukas, Gerald T.; Halstead, Bruce G.; Oregon. Fish Commission. Division of Management and Research,; Oregon. Department of Fish and Wildlife, (Oregon Fish Commission of Oregon, Division of Management and Research, 1976)
http://hdl.handle.net/1957/28842
Keywords: Baltic clam=Macoma balthica; bent-nose clam=Macoma nasuta; butter clam=Saxidomus giganteus; cockle clam=Clinocardium nuttallii; commercial fisheries - shellfish; Coos Bay; gaper clam=Tresus capax; Irus clam = Irus ishibashianus; Littleneck clam = Leukoma staminea; molluscs; Nehalem Bay; Nestucca Bay; Netarts Bay; recreational fisheries - shellfish; Red abalone = Haliotis rufescens; Salmon River Estuary; Siletz Bay; softshell clam=Mya arenaria; Tillamook Bay; Yaquina Bay

The bay clams of Oregon: their economic importance, relative abundance, and general distribution - Marriage, Lowell D.; Oregon. Fish Commission (Contribution (Oregon. Fish Commission), 1954)
Keywords: abundance; Alsea River estuary; aquatic invertebrates; bent-nose clam=Macoma nasuta; biological; bivalves; Bodega tellin=Tellina bodegensis; butter clam=Saxidomus giganteus; catch statistics; commercial fisheries - shellfish; Coos River estuary; Coquille River estuary; economics; fat gaper=Tresus capax; general; geographical distribution; molluscs; Nehalem River estuary; Nestucca River estuary; Netarts estuary; new species description; Nuttall cockle=Clinocardium nuttallii; Pacific littleneck=Leukoma staminea; Pacific razor=Siliqua patula; recreational fisheries - shellfish; Salmon River estuary; Siletz River estuary; Siuslaw River estuary; softshell clam=Mya arenaria; Tillamook estuary; Umpqua River estuary; white-sand macoma=Macoma secta; Yaquina Bay

Ghost shrimp (Shellfish Program Special Report, 1951)
Keywords: commercial fisheries - shellfish; crustaceans; general; Ghost shrimp = Neotrypaea californiensis (Callianassa californiensis); recreational fisheries - shellfish

The present status of the bay clams in Oregon (Oregon Fish Commission. Shellfish Program special report, 1948)
Keywords: Alsea Bay; Butter clam = Saxidomus giganteus; Cockle clam = Clinocardium nuttallii; commercial fisheries - shellfish; Coos Bay; Gaper clam = Tresus capax; Littleneck clam = Leukoma staminea; natural resource management; Nehalem Bay; Nestucca Bay; Netarts Bay; recreational fisheries - shellfish; Salmon River Estuary; Siletz Bay; Softshell clam = Mya arenaria; spatial distribution; Tillamook Bay; Umpqua River estuary; Yaquina Bay